Sinergitas Program Vokasi di Madrasah Sebagai Lifeskill Menghadapi Era Globalisasi - Nurdiana, Ira (Revorma: Jurnal Pendidikan dan Pemikiran, 2023)
In an era of rapidly growing globalization, there is increasing competition in many areas, from goods, services, to human resources. To be able to prosper in the age of globalization, it would require competitive human resources. In practice, the quality of human resources becomes one of the determining factors in achieving the success of a job, so individual surplus in any form is urgently needed. In this study the author analyzes how the relationship to the effectiveness of the vocation program in  madrasah can support the lifeskill of students in the face of the era of globalization. This article uses library research methods, by studying some primary legal material such as books, journals, or magazines to gather data.